2014
DOI: 10.1108/nfs-06-2013-0075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the satiating properties of a fish protein hydrolysate among overweight women

Abstract: Purpose – This paper aims to investigate the satiety properties of a fish protein hydrolysate (blue whiting muscle hydrolysate, BWMH). Protein consumption is associated with higher satiety, protein being considered as the more satiating macronutrient. This property is extensively investigated in regard to weight management. Design/methodology/approach – Fifteen overweight women were included in a crossover design study. Subjects consumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Our results confirm the previous in vitro and in vivo ( 26 28 ) results of the efficacy of a FPH, Slimpro ® , obtained from blue whiting ( M. poutassou ) muscle by enzymatic hydrolysis in stimulating the secretion of CCK and GLP-1. Moreover, Slimpro was effective on body weight and particularly in controlling body composition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm the previous in vitro and in vivo ( 26 28 ) results of the efficacy of a FPH, Slimpro ® , obtained from blue whiting ( M. poutassou ) muscle by enzymatic hydrolysis in stimulating the secretion of CCK and GLP-1. Moreover, Slimpro was effective on body weight and particularly in controlling body composition.…”
Section: Discussionsupporting
confidence: 91%
“…The increase of CCK and GLP-1 was statistically significant when compared with placebo without any differences among the two tested doses. The results obtained in this study confirmed the preliminary results obtained in the earlier in vitro and in vivo studies carried out on blue whiting FPH Slimpro ( 26 28 ). As a consequence of FPH consumption, body composition was changed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, since this was a study population with older adults who lived in a nursing home setting, the results are not directly transferable to our study population with homedwelling older adults. Based on a few previous studies investigating the effect of supplements containing protein hydrolysates from fish on metabolic health (17,26) , we hypothesised that small doses of CPH may be effective due to the content of small, easily absorbable bioactive peptides. These are capable of rapidly affecting different metabolic pathways involved in glucose regulation and hence leading to a more rapid glucose response in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were found that investigated the impact of FPH on subjective appetite ratings and/or circulating appetite hormones in healthy adults [69,70,76,79]. The earliest investigation by Zaïr et al [79] found no significant differences between a blue whiting-derived FPH and PLA on area under the curve (AUC) subjective hunger perceptions or biomarkers of appetite/satiety including plasma cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1). Similarly, no difference in ad libitum energy intake was found between conditions.…”
Section: Appetite Regulationmentioning
confidence: 99%